Biotechnological applications of microalgae :boidiesel and value-added products - Bux, F. (CRC Press, 2013)
"The book gives an in-depth analysis of microalgal biology, ecology, biotechnology and biofuel production capacity as well as a thorough discussion on the value added products that can be generated from diverse microalgae. It summarizes the state of the art in microalgal biotechnology research, from microalgal strain selection, microbiology, cultivation, harvesting, and processing. Contributors from the US, Africa, Asia, South America, and Europe cover microalgal physiology, biochemistry, ecology, molecular biology, and more"--